Peg + Cat. A totally awesome Halloween [videorecording (DVD)]. (PBS Kids, 2015)
It's Halloween and Peg and Cat have a big problem! Someone has left the park full of trash and the costume parade might be canceled. Don't freak out, Peg and Cat save the day by sorting and recycling. Then, they discover they've been trick-or-treating with a real, live tiger!